Cost Implications of Naira Notes Redesign on Household and Money Market Operators in Taraba State (Proceeding of the International Conference on Economics, Accounting, and Taxation, 2024)
This research work investigates cost implication of change in Naira notes on Household and money market operators in Taraba State. The study adopted a survey research design to obtain data about practices, situations, and views through questionnaires. The number of respondents for Households and Money Market Operators is 394 and 338 respectively. The study used a simple multistage and cluster sampling method to select the sample respondents. The study employed a descriptive statistic method; simple percentages and the Chi-square (x2) statistic were used for the computation and analysis of the data collected. The study found a significant increase in general costs of household and money market operators in Taraba State between 2022 and 2023. This policy significantly affected households and money market operators in Taraba State by increasing their general costs. The study recommends that a reasonable timeline be given to the implementation period with strict monitoring and control of commercial banks to erode favoritism and corruption in the process of policy implementation. There should be stability in the maximum cash withdrawal policy from all means: Point of sale (POS), automated teller machines (ATM) over the bank counter, etc., and adequate provisions for electronic banking for rural and urban centers should be made by financial sector administrators. The government should promote ceaseless cash traceability and accountability to keep the new notes as close to the banking system as possible.